Pengaruh Harga, Variasi Produk, Kualitas Produk, dan Kualitas Pelayanan terhadap Keputusan Pembelian Ulang UMKM Gita - Salsabila Khendra; Anadda Nikita Shani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
MSMEs (Micro, Small and Medium Enterprises) are one of the factors that encourage Indonesia's progress in the current economic field. One of the MSMEs in Indonesia is Jajanan Neng Gita which is engaged in the culinary field. The competition that occurs in the culinary field is very competitive to be able to attract repurchases made by consumers. The purpose of this study was to determine the influence of price, product variation, product quality and service quality on repurchase decisions. The method in this study used quantitative methods to the respondents of MSME Jajanan Neng Gita. The required data was collected through a questionnaire (Google Form) with the number of respondents in this study was 80 people. The results obtained from this study are the influence of Price, Product Variation, Product Quality and Service Quality on the Decision to Repurchase MSMEs of Neng Gita Snacks.